Discovering the universe - Comins, Neil F; Comins, Neil F; Kaufmann, William J (New York, W H Freeman and Company, 2008)
Discovering the Universe is the bestselling brief text for descriptive one-term astronomy courses (especially those with no mathematics prerequisites). Carried along by the book's vibrant main theme, "the process of scientific discovery," the Eighth Edition furthers the book$1 (Bs legacy for presenting concepts clearly and accurately while providing all the pedagogical tools to make the learning process memorable.s
Appendices A1-A21p.; Glossary G1-G16p.; Index I1-I14p.